Potential of space in the educational process - Kokanović, Tihana (Rethinking childhood II: child and space, 2026)
Stimulating environment empowers the development of every child’s full potential. Children who interact with their surroundings develop creative and productive traits that become the foundation for active reasoning, research and development of individual potential. Highly equipped and developmentally oriented space is an unquestionable characteristic of the community that cares for, supports, and motivates quality approach directed to active learning of the child. Preschool institutions should become or remain a place designed to suit children by supporting all their educational needs. It is a challenge that requires not only great responsibility of experts but also careful observation, planning, and structuring of incentive environment in order to develop the child’s overall potential appropriately. Since space—i.e., comprehensively and qualitatively designed preschool environment—presents an important factor of overall children’s development, preschool teachers should, together with children, design and structure this environment so that it motivates creativity and research, propels curiosity, awakens interest and empowers the development of all children’s potentials. This work examines the pedagogical formation of quality spatial-material environment that, as such, motivates active children’s learning and stimulates their overall development. In the theoretic sense, the work is oriented towards constructivistic and co-constructivistic paradigm, as a stronghold of the contemporary concept of children as active and engaged (co)creators of appropriate and developmentally supportive preschool environment.